Need for velopharyngeal surgery after primary palatoplasty in cleft patients. A retrospective cohort study and review of literature. (September 2021) - Tache, Ana; Maryn, Youri; Mommaerts, Maurice Y.
Abstract: Background: Enabling intelligible speech plays an important role in achieving social inclusion and a good quality of life of cleft patients. A crude measure of primary palatal repair quality is the incidence of operations to correct velopharyngeal insufficiency (VPI) after speech-language therapy has proven inadequate. This study assessed the necessity for surgery to correct velopharyngeal insufficiency following our standardized two-staged protocol, compared the results with the literature, and identified factors that may influence velopharyngeal competence. Methods: A review of the literature was performed. The outcome measure in our series was the necessity for a secondary procedure to correct velopharyngeal insufficiency. The results of literature review were compared with the results of our case series, which we treated using a standardized protocol. Results: In our retrospective study, 5 patients (2.5%) required secondary pharyngoplasty. In literature, the frequency of surgery to correct velopharyngeal insufficiency after one- and two-stage protocols were 13.6% and 24.5%, respectively. No statistical difference was found between bilateral and unilateral clefts. The frequencies of velopharyngeal surgery were 7.2% after Furlow palatoplasty, 17.5% after a 2-flap palatoplasty, 18.6% after a Wardill-Killner palatoplasty, and 35.6% after a Von Langenbeck palatoplasty. Conclusion: The literature reported that one-stage palatoplasty is correlated with a lower incidence of secondary pharyngeal surgery. Our standardized two-stage protocol proved successful in avoiding secondary velopharyngeal surgery but due to the reduced number of patients included in our study, more research is needed. Highlights: A crude measure of primary palatal repair quality is the incidence of pharyngoplasty. Following our standardized two-stage protocol, 2.9% patients required secondary pharyngoplasty. In literature, the frequency of pharyngeal surgery after one-stage protocol was 13.6%. In literature, the frequency of pharyngeal surgery after a two-stage protocol was 24.5%.